The call to serve the life of an American president, George Herbert Walker Bush - Meacham, Jon 1969- (Random House, 2024)
"The lavishly illustrated The Call to Serve is an intimate, illuminating portrait of the 41st U. S. President, a man many know mainly through his politics. Jon Meacham brings the leader vividly to life, including as a man dedicated to political and moral leadership, and to a life marked by the strong values of integrity and respect for others that Bush learned during his childhood. Bush pursued a life of service to America and to others, including through action in the Pacific during World War II, his political rise to Congressman in Texas, then his serving as U. S. Ambassador to the UN, director of the CIA, Vice President during the administration of Ronald Reagan, and as President. Set against the historical background of periods in America during the 20th and 21st century, this book celebrates the legacy of a man many people do not know, whose bedrock beliefs in honesty and respect for the dignity of others led to a life of leadership viewed as a call to serve. Obama said towards the end of Bush's life that he put the country first, throughout his life, 'both before he was president, while he was president, and ever since'"--
Keywords: Bush, George -- 1924-2018; Bush, George / 1924-2018; Presidents / United States / Biography; United States / Politics and government / 1945-1989; United States / Politics and government / 1989-; États-Unis / Politique et gouvernement / 1945-1989; États-Unis / Politique et gouvernement / 1989-; Biographies; Biografie; Bildband